Musculoskeletal asymmetry in football athletes: a product of limb function over time - Hart, N. H.; Nimphius, S.; Weber, J.; Spiteri, T.; Rantalainen, T.; Dobbin, M.; Newton, R. U. (Medicine & Science in Sports & Exercise, 2016)
Purpose: Asymmetrical loading patterns are commonplace in football sports. Our aim was to examine the influence of training age and limb function on lower-body musculoskeletal morphology.